A Hybrid Eukaryotic–Prokaryotic Nanoplatform with Photothermal Modality for Enhanced Antitumor Vaccination. Issue 16 (28th February 2020) - Chen, Qi; Huang, Guojun; Wu, Wangteng; Wang, Jianwei; Hu, Jiawei; Mao, Jianming; Chu, Paul K.; Bai, Hongzhen; Tang, Guping
Abstract: Cytomembrane‐derived nanoplatforms are an effective biomimetic strategy in cancer therapy. To improve their functionality and expandability for enhanced vaccination, a eukaryotic–prokaryotic vesicle (EPV) nanoplatform is designed and constructed by fusing melanoma cytomembrane vesicles (CMVs) and attenuated Salmonella outer membrane vesicles (OMVs). Inheriting the virtues of the parent components, the EPV integrates melanoma antigens with natural adjuvants for robust immunotherapy and can be readily functionalized with complementary therapeutics. In vivo prophylactic testing reveals that the EPV nanoformulation can be utilized as a prevention vaccine to stimulate the immune system and trigger the antitumor immune response, combating tumorigenesis. In the melanoma model, the poly(lactic‐ co ‐glycolic acid)–indocyanine green (ICG) moiety (PI)‐implanted EPV (PI@EPV) in conjunction with localized photothermal therapy with durable immune inhibition shows synergetic antitumor effects as a therapeutic vaccine. The eukaryotic–prokaryotic fusion strategy provides new perspectives for the design of tumor‐immunogenic, self‐adjuvanting, and expandable vaccine platforms. Abstract : To improve the functionality and expandability of biomimetic nanoplatforms for cancer therapy, a eukaryotic–prokaryotic vesicle (EPV) is engineered by fusing melanoma cytomembrane vesicles and attenuated Salmonella outer membrane vesicles. Inheriting the virtues of the parent ingredients, the EPV integrates tumor antigens with natural adjuvants, exhibiting great potential for immunotherapy. Moreover, it can be readily functionalized with complementary therapeutics for enhanced anticancer vaccination.